Modelling the impact of innovation performance on digital competitiveness: The key role of innovation and technologies - Kiselakova, Dana; Sofrankova, Beata; Gombar, Miroslav; Matijova, Maria (Asian Economic and Financial Review, 2024)
The objective of this paper is to evaluate the innovation and digital competitiveness of the EU-27 countries and to reveal the effect of innovation performance on the changes in digital competitiveness. We obtained secondary data from the annual reports of the Global Innovation Index (GII), Summary Innovation Index (SII), and Digital Economy and Society Index (DESI) for the years 2017 to 2021. Using structural equation modeling, the main concept was to develop a new variable, Innovation Performance (IP), which was created by combining the indices of the GII and SII dimensions within a new three-factor model. The modelling findings revealed that both indexes had a statistically significant impact on the variations in the IP value, with the SII exerting a greater influence compared to the GII. The IP variable in the modified model has a significant positive impact on the change in the score of the DESI. We found a positive impact for 10 dimensions (from 19) and a negative impact for firm investments. The highest positive impact was confirmed for research systems, information technologies, and human resources. Our findings also highlight real economic contexts and drivers for EU countries' strategies and policies in the progress of digital competitiveness.